Effects of UV irradiation and thermal annealing on LiCl derivatives encapsulation in porous PET membranes coated with a thin Au film. Issue 1 (1st February 2022) - Vacik, J.; Ceccio, G.; Cannavò, A.; Lavrentiev, V.
Abstract : Encapsulation of LiCl (LiCl derivatives) in porous Au-coated PET membranes after UV irradiation or thermal annealing was studied by ion and neutron beam analytical techniques. The shape of the pores in the PET membranes before and after LiCl doping were characterized by Ion Transmission Spectroscopy that enabled to describe their 3D geometry and filling after exposing to a LiCl aqueous solution. The content and depth distribution of Li (and Cl) in pores was examined by Neutron Depth Profiling (NDP). Using the ITS and NDP complementary methods, it was possible to determine the amount of lithium incorporated in the pores and assess the ability of the PET membranes (modified by UV irradiation or thermal annealing) to encapsulate lithium atoms (LiCl derivatives). The present study could be relevant to technology of porous separators for thin lithium ion batteries.